### Math MCQ - English

# If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then

Home | Discussion Forum** If the roots of the equation (b - c)x2 + (c - a)x + (a-b) = 0 are equal, then**

2b = a + c

a = b = c

b2 = ac

none of these

Answer : A

** View More Related Question**

** 2) If the third term of an AP is 12 and the seventh term is 24, then the 10th term is**

** 3) A number 15 is divided into three parts which are in AP and sum of their squares is 83. The smallest part is**

** 4) Second term of sequence with general term n2 - 4/2 is**

** 5) A.P whose nth term is 2n-1 is**